2dy/dx-2y=x5sin2x-x3+4x4
To solve linear equation :
"2\\frac{dy}{dx}-2y=x^5\\sin{2x}-x^3+4x^4"
Lets divide both sides of equation by 2 and multiply both sides by "f(x)=e^{\\int-1dx'}=e^{-x}"
"e^{-x}\\frac{dy}{dx}-e^{-x}y=\\frac{e^{-x}}{2}(x^5\\sin{2x}-x^3+4x^4)"
Lets substitute "-e^{-x}=\\frac{d}{dx}(e^{-x})"
"e^{-x}\\frac{dy(x)}{dx}+\\frac{d}{dx}(e^{-x})y(x)=\\frac{1}{2}e^{-x}(x^5\\sin{2x}-x^3+4x^4)"
Apply the reverse product rule "f\\frac{dg}{dx}+g\\frac{df}{dx}=\\frac{d}{dx}(fg)" to left-hand side:
"\\frac{d}{dx}(e^{-x}y(x))= \\frac{1}{2}e^{-x}(x^5\\sin{2x}-x^3+4x^4)"
Integrate both sides with respect to x:
"\\int\\frac{d}{dx}(e^{-x}y(x))dx= \\int\\frac{1}{2}e^{-x}(x^5\\sin{2x}-x^3+4x^4)dx"
Evaluate the integrals:
"e^{-x}y(x)= \\frac{1}{6250}e^{-x}(-3125(4x^4+15x^3+45x^2+90x+90)-2\\cos(2x)(625x^5+1250x^4-500x^3-3600x^2-2280x+528)+(-625x^5+1875x^4+5500x^3+2100x^2-4920x-2808)\\sin(2x))+c_1"
by dividing both sides by "e^{-x}"
"y(x)= \\frac{e^x}{6250}e^{-x}(-3125(4x^4+15x^3+45x^2+90x+90)-2\\cos(2x)(625x^5+1250x^4-500x^3-3600x^2-2280x+528)+(-625x^5+1875x^4+5500x^3+2100x^2-4920x-2808)\\sin(2x))+c_1"
Comments
Leave a comment